Evaluation of hydrolysis conditions for the recovery of urinary metabolites of common pharmaceutical drugs - Ong, Felicia Jin Ling (2014)
Clinical and forensic toxicology involves the identification and/or quantitation of drugs and poisons in biological specimens, with urine being the most commonly used. Although chromatographic techniques were able to identify drugs in urine, it was difficult to detect both the parent drug and its glucuronidated metabolites simultaneously, due to differences in their polarity. Also, many drugs exist largely as their glucuronide conjugates, with only traces of parent drugs found in urine. Hence, to increase detectability of most drugs, the use of β-glucuronidase enzyme was proposed. Hydrolysis with β-glucuronidase should hydrolyse glucuronide conjugates and liberate the parent drug, increasing free drug concentration in the urine. This would allow better detection by chromatography. Enzyme hydrolysis conditions were evaluated, and β-glucuronidase extracted from Haliotis rufescens gave the best recovery of parent drug from its glucuronide conjugates, following incubation at pH 5.0 for 3 hours at 60oC. Application of these parameters onto case samples showed promising results for acidic and basic drugs, with benzodiazepines showing exceptional results. All enzyme-hydrolysed benzodiazepine samples showed increased free drug levels. Case samples whose initial chromatogram reflected benzodiazepine-negative result, yielded benzodiazepine-positive result post-hydrolysis. Therefore, hydrolysis with β-glucuronidase was an efficient method to increase chromatography sensitivity towards drugs, especially benzodiazepines.